Assessment on the innovative development of an ancient village from the perspective of holistic governance: A case study of six ancient villages in China - Xing, Qinfeng (Frontiers in Environmental Science, 2022)
Innovative development has been the favorite subject of social governance with the aim of helping the modernization transformation of the governance system and governance capacity for the rural revitalization in China. Therefore, an evaluation indicator system is introduced to estimate the innovative development of ancient village from the perspective of holistic governance. The factor characteristics of 11 indicators are verified statistically by using data on Yixian ancient villages (China). It finds that: 1) The dominant impact factors between factor analysis and resistance diagnosis have the characteristic of identity; 2) The relative importance of “four-dimensional linkage” is different and feasible. The finding is conductive to understand the concept of “harmony, cooperation and convergence” and some strategies are proposed as follow: Highlighting the demand orientation of “good” life; Creating a social pattern of “co-construction, co-governance and sharing”; Optimizing the organization coordination of “multi-dimensional linkage”; Sticking to the development background of “original taste”.